Effect of multilateral trade liberalization on export performance in developing countries: Does aid for trade matter?. Issue 2 (3rd June 2019) - Gnangnon, Sena Kimm
Abstract : Purpose: The purpose of this study is to examine empirically whether the impact of multilateral trade liberalization on export performance and export performance convergence in developing countries depends on the amount of Aid for Trade (AfT) flows that accrue to these countries. Export performance is measured by export of goods and services to gross domestic product ratio, whereas export performance convergence refers to the process whereby a developing country's export performance catches up with the world's average export performance. Design/methodology/approach: The analysis has used an unbalanced panel data set covering a sample of 97 developing countries, over the period 2002 to 2015. The two-step system generalized methods of moments has been used to address the question empirically. Findings: Empirical results show that multilateral trade liberalization generates higher export performance and convergence in export performance in developing countries only when it is accompanied by higher AfT flows to developing countries, with a view of helping these countries enhance their trade capacity and reap the opportunities offered by multilateral trade liberalization in the international trade market. Research limitations/implications: These findings indicate that greater access to the international trade market is not sufficient to promote developing countries' export performance and convergence in export performance. Such a promotion could materialize if multilateral trade liberalization is accompanied by higher AfT flows (to enhance these countries' capacity to trade). The findings therefore indicate that the current context of escalation of trade tensions would likely result in lower degree of multilateral trade liberalization, and eventually lower AfT flows to recipient-countries, and ultimately hamper developing countries' export performance and convergence in export performance. Practical implications: The findings therefore indicate that the current context of escalation of trade tensions would likely result in lower degree of multilateral trade liberalization, and eventually lower AfT flows to recipient-countries, and ultimately hamper developing countries' export performance and convergence in export performance. An avenue for future research could be to perform the same analysis when data would be available over a longer time period. Future studies on the matter could also investigate whether the findings obtained apply to components of export performance, including for example manufactured exports and non-manufactured exports. Originality/value: Many papers related to the AfT effectiveness have looked at the effect of AfT inflows on recipient-countries' export performance. However, little attention has been paid to the effect of multilateral trade liberalization on developing countries' export performance and export performance convergence and particularly to whether this effect would depend on the amounts of AfT that would accrue to developing countries to help them develop their trade capacity. To the best of our knowledge, no previous paper has addressed this issue.